Comparison Study of Ionic Gelation and SNEDDs Method in the Preparation of Cocoa Peel Extract Nanoparticles as Antibacterial Against Klebsiella pneumonia - Ratih Lestari; Tatang Shabur Julianto; Yandi Syukri; Aditya Sewanggara Amatyawangsa Wicaksana; Iqmal Tahir (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Cocoa peel is the primary waste from chocolate production. It contains flavonoids that can inhibit the growth of Klebsiella pneumonia which causes chronic bronchitis. This study aims to obtain cocoa peel extract nanoparticles for antibacterial caused by K. pneumonia. The isolation of flavonoids was done using the maceration method in 96% ethanol. Phytochemical and Thin Layer Chromatography (TLC) analyses have been used to identify the active compounds contained in the extract. Flavonoid levels have been investigated using UV-Visible spectrophotometry. The preparation of nanoparticles from cocoa peel used ionic gelation and Self-Nano Emulsifying Drug Delivery System (SNEDDS). The nanoparticle obtained has been analyzed for particle size and polydisperse index. In vitro test was carried out to determine the antibacterial activity of K. pneumonia. Identification of active compounds using a UV-Visible spectrophotometer showed that cocoa peel extract contained flavonoids of 6.33%. Nanoparticle preparations using the SNEDDS method were more optimal than the ionic gelation method, with particle sizes 135.2 nm (4%), 156.1 nm (12%), and 235.3 (20%). Based on the in vitro test, nanoparticles from cocoa peel extract were able to inhibit the growth of K. pneumonia.